Stopped Flow Kinetics of MnII Catalysed Periodate Oxidation of 2, 3- dimethylaniline - Evaluation of Stability Constant of the Ternary Intermediate Complex - Rajneesh D. Kaushik; Richa Agarwal; Priyanka Tyagi; Om Singh; Jaspal Singh (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2015)
The formation of ternary intermediate unstable complex during the oxidation of aromatic amines by periodate ion catalysed by MnII has been proposed in case of some anilines. This paper is the first report on stopped-flow kinetic study and evaluation of stability constant of ternary complex forming in the MnII - catalysed periodate oxidation of 2, 3-dimethylaniline (D) in acetone-water medium. Stop-flow spectrophotometric method was used to study the ternary complex formation and to determine its stability constant. The stop-flow trace shows the reaction to occur in two steps. The first step, which is presumably the formation of ternary complex, is relatively fast while the second stage is relatively quite slow. The stability constant evaluated for D - MnII - IO4- ternary complex by determining equilibrium absorbance is (2.2 ± 1.0) × 105. Kinetics of ternary complex formation was defined by the rate law(A) under pseudo first order conditions.ln[C2]eq / ( [C2]eq -[C2]) = kobs . t (A)where, kobs is the pseudo first order rate constant, [C2] is concentration of ternary complex at given time t, and [C2]eq is the equilibrium concentration of ternary complex.